Central Nervous System Involvement in Systemic Autoimmune Rheumatic Diseases—Diagnosis and Treatment - Juncker, Aline Santana; Appenzeller, Simone; de Souza, Jean Marcos (Pharmaceuticals (Basel, Switzerland), 2024)
Central nervous system (CNS) involvement in autoimmune rheumatic diseases represents a significant challenge for clinicians across all specialties. While most reviews on the subject focus on neurological manifestations within a specific rheumatic disease, few descriptions shift from neurological clinical syndromes to achieve rheumatological diagnoses. This narrative review aims to synthesize current knowledge on the diagnosis and management of CNS manifestations occurring in the most prevalent rheumatic conditions in adults. We searched the MEDLINE database using the terms “central nervous system”, “rheumatic diseases”, “systemic lupus erythematosus”, “rheumatoid arthritis”, “Sjögren syndrome”, and “vasculitis”. The search strategy included review articles from 2019 to 2024, published in English, Spanish, or Portuguese. We explored the pathophysiological mechanisms linking autoimmunity to CNS pathology, emphasizing the role of syndromic reasoning, autoantibody profiles, and imaging modalities as tools for diagnosis and determination of inflammatory activity. The review also discusses differential diagnoses through a stepwise approach to neurological syndromes, summarized in diagnostic flowcharts, and presents updated treatment options. Although our approach is primarily semiology-based, the complexity of the subject invites future endeavors involving new technologies, such as functional MRI, MR spectroscopy, and nuclear medicine.